Implementasi Aplikasi Arkas Dalam Pengelolaan Dana BOSP Pada SMA Negeri Terakreditasi A Di Kabupaten Pesisir Selatan - Gian Syaputra; Ingra Sovita (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
The management of School Operational Assistance Funds (BOSP) requires transparency, accountability, and efficient financial administration in schools. To support this objective, the government introduced the School Activity and Budget Planning Application (ARKAS) as a digital system for school financial management. This study aims to analyze the implementation of ARKAS in managing BOSP funds at A-accredited public senior high schools in Pesisir Selatan Regency. The research employed a descriptive qualitative approach. Data were collected through interviews, observation, and documentation involving school principals and BOSP treasurers from 16 public senior high schools. The results show that ARKAS has been implemented in three stages of financial management, namely planning, implementation, and reporting. In the planning stage, schools prepare the School Activity and Budget Plan (RKAS) through the ARKAS system. During implementation, financial transactions are recorded digitally within the application. Reporting activities are conducted through ARKAS by uploading supporting financial documents. However, several challenges were identified, including technical application disturbances, limited human resource capacity, administrative workload, and teachers serving dual roles as treasurers. Schools address these challenges through task distribution, internal coordination, and workflow adjustments. Overall, ARKAS implementation contributes to improving transparency and accountability in school financial management, although its effectiveness is influenced by the technical capacity and organizational readiness of each school.